2021
DOI: 10.1021/acsnano.1c06299
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Thermal Transport across Layered Graphene–MoS2 Superlattices

Abstract: Layering two-dimensional van der Waals materials provides a high degree of control over atomic placement, which could enable tailoring of vibrational spectra and heat flow at the sub-nanometer scale. Here, using spatially resolved ultrafast thermoreflectance and spectroscopy, we uncover the design rules governing cross-plane heat transport in superlattices assembled from monolayers of graphene (G) and MoS2 (M). Using a combinatorial experimental approach, we probe nine different stacking sequences, G, GG, MG, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 51 publications
(89 reference statements)
2
22
0
Order By: Relevance
“…Interestingly, despite the discrepancy, finite elastic and inelastic phonon transmission , across the 2D material interfaces is presumed to be solely responsible for the observed thermal boundary resistance in all prior studies. Often, the disparity in the thermal resistance values is attributed to different transmission probability of phonons at the interfaces due to the presence of capping layer , and/or different interface quality, , as a small change in the van der Waals gap between 2D materials and substrates could affect the interfacial thermal transport …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, despite the discrepancy, finite elastic and inelastic phonon transmission , across the 2D material interfaces is presumed to be solely responsible for the observed thermal boundary resistance in all prior studies. Often, the disparity in the thermal resistance values is attributed to different transmission probability of phonons at the interfaces due to the presence of capping layer , and/or different interface quality, , as a small change in the van der Waals gap between 2D materials and substrates could affect the interfacial thermal transport …”
Section: Introductionmentioning
confidence: 99%
“…Often, the disparity in the thermal resistance values is attributed to different transmission probability of phonons at the interfaces due to the presence of capping layer 26,27 and/or different interface quality, 17,24 as a small change in the van der Waals gap between 2D materials and substrates could affect the interfacial thermal transport. 28 In addition to the aforementioned explanations, another possible explanation to the discrepancy in the measured R, which was ignored in most prior analysis, is that phonons are not in local thermal equilibrium during Raman measurements. In typical Raman measurements, 2D materials are heated by laser irradiation 13−15 or electrical heating 16−18 while the steady-state temperatures of vibrational modes in the 2D materials are monitored from either shifts of the Raman peaks or intensity ratios of Stokes and anti-Stokes peaks.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 68 ] The reason for the high ZT in 2D crystals is likely due to the anharmonic bonding and poor interlayer interactions that result in very low thermal conductivity. [ 67 ] Stacked 2D crystal heterostructures can exhibit much lower out‐of‐plane thermal conductivity due to vibrational mismatch and increased interlayer spacing, [ 69 ] and thus can have higher ZT. Novel unexplored 2D tetragonal pnictogen (P, As, Sb, or Bi) crystals have also been predicted by combined density functional theory and machine learning (ML) analysis to have very high thermoelectric constants (ZT ≈ 3.22 for 2D tetragonal Sb) with high thermoelectric conversion efficiency due to their very low lattice thermal conductivity.…”
Section: Energy Conversion Mechanisms In Layered 2d Crystalsmentioning
confidence: 99%
“…8,11−13 Additionally, such flakes are most likely to have defects or contamination, which further create additional phonon scattering centers in the films. Nevertheless, recent works have demonstrated high thermal isolation across a few micrometer size exfoliated graphene/MoSe 2 /MoS 2 /WSe 2 heterostructures, 13 graphene/ MoS 2 SLs, 8 and polycrystalline WS 2 films. 10 In contrast, bottom-up epitaxial techniques, such as molecular beam epitaxy (MBE), enable wafer-scale growth of high-order vdW SLs with atomically smooth and abrupt periodic interfaces.…”
mentioning
confidence: 99%
“…Despite significant efforts toward this direction, many experimental studies have reported vdW stacks using top-down fabrication methods, such as exfoliation, which can only prepare small flakes on a micrometer scale. , Additionally, such flakes are most likely to have defects or contamination, which further create additional phonon scattering centers in the films. Nevertheless, recent works have demonstrated high thermal isolation across a few micrometer size exfoliated graphene/MoSe 2 /MoS 2 /WSe 2 heterostructures, graphene/MoS 2 SLs, and polycrystalline WS 2 films .…”
mentioning
confidence: 99%